Singularidade, pluralidade e igualdade: elementos constitutivos da liberdade política em Hannah Arendt. - Diehl, Daniela Bidin (2019)
This research has as its main theme the constitutive elements of political freedom, based on the analysis of the political theory of the thinker Hannah Arendt (1906-1975), especially the concepts of singularity, plurality and equality. When we think of such constitutive elements, with regard to the conception of equality, we immediately have the idea of struggle for rights, social justice, that is, an equality based on the ideals of positive law. It is pertinent to evoke such struggles, but within the constituent elements of politics the concept of equality is much broader. According to the thinker, with regard to the conception of equality, we realize that there are singular aspects, since we conceive it to be fundamentally a social construction, and not a condition in which we are already born; For Arendt we were not born equal and, therefore, we are primarily singular subjects who equalize from the construction of a participatory coexistence in the political community. This participation takes place through action and discourse and, for this to happen, it is necessary to access the individual to appear in the community. This public exposition is a condition of both the manifestation of its uniqueness and the guarantee of equality. In this appearance the subject exposes his singularity in the midst of plurality. However, if there are no adequate public spaces or individuals are prevented from participating in them, their uniqueness in relation to other individuals and even the necessary assumptions for the legitimation of equality are compromised. One of the biggest problems is when individuals imagine that matching one another is simply meeting the need for belonging. In this way the subjects become indifferent in relation to political issues but, simultaneously, seek to identify with a collective, generating the mass phenomenon. Thus we have a mix of apparently politically neutral people, susceptible to the culture of consumption and the needs of the labor. In this context the totalitarian movement finds fertile ground to install domination and oppression and their hideous faces on the masses. Understanding how Arendt thematizes the assumptions that enable the phenomenon of the masses, as a condition for the installation of totalitarianism and how plurality / uniqueness from the conception of equality can be antidotes to this tendency, is what we intend in this dissertation. To this end, we will first address the three fundamental human activities of Vita Activa namely: labor, work and action. From the analysis of the Arendtian work, we will seek to reflect on what are the probabilities of manifestation of totalitarianism and its possible occurrences today. We will develop the relationship between freedom and equality, where through researching the birth concept proposed by the thinker, we infer that to actually experience freedom it is essential to be in an egalitarian space. However, not an equality understood as uniformity but a manifestation of our individualities with the community. From the available theoretical elements regarding the constitutive elements of political freedom, we will look at the meaning of politics. Finally, we seek to launch ideas and perspectives on the modern-contemporary world and on political praxis today.